SIHAT: simplifying interfaces in health-nets for achieving telemetry - Ashraf, Qazi Mamoon; Habaebi, Mohamed Hadi; Chebil, Jalel (Pak Publishing Group, 2014)
Telemetry in healthcare refers to an autonomic process by which remote measurements of patients are taken and transmitted from non-Internet Protocol based equipment for monitoring purposes. The transmission is through specialized channels of communication using non-standard, proprietary processes. Internet of Things, an expansion of wireless sensor network technologies, aims to standardize the communication methods between such devices. The application of wireless sensor networks in healthcare is referred to as Health-Nets where networked sensors are deployed on a person‟s body to monitor vital functions. This paper discusses early work for a messaging communication system in an attempt to make Health-Nets compatible with the IoT by simplifying the interfaces. Concerns of data management, addressing, IoT telemetry and the corresponding security requirements are addressed as well. Preliminary observations of performance on a testbed are presented.